(untitled) (Global Journal of Science Frontier Research, 2020)
Based on measurements, the author describes and explains the detrimental effect of negative thinking on the health of the negatively thinking individual, as well as the detrimental effect of negatively thinking individuals on other individuals. The article also describes and explains the detrimental effect of negative thinking and negative emotions (fear, hatred, anger, etc.) on the magnetic field of the Earth. 500 million scared individuals can lower the magnetic field of the Earth to the degree of causing a magnetic storm and our immune system is ruled electromagnetically through our nonlinear electromagnetic field (NEMF), which rules and regulates everything in the body including the immune system. In time of pandemic, like the one we have now, it is essential to stay calm and think positively because panic and fear are paralyzing emotions, which will decrease our immune abilities and make us victims of the virus. So, stay calm, do not allow to be scared if you want to survive the pandemic. Don’t be scared be prepared.